Publications Received (Academy of Management Review, 1991)
The article presents a list of books related to management. They include “America's Work Force is Coming of Age,” by Catherine D. Fyock, “Careers and Corporate Cultures: Managerial Mobility in Large Corporations,” by Hugh Gunz, and “The critical Path to Corporate Renewal,” by Michael Beer, Russell A. Eisenstat, and Bert Spector.